DISTRIBUTION OF ERWINIA AMYLOVORA ON WILD AND CULTURALLY GROWN APPLE TREES MALUS SPP. FOR THE PERIOD OF 2021 - Malakhova , N.P.; Skiba, Y.A.; Tezekbayeva , B.K.; Khasseyn , A.; Dmitriyeva , K.A.; Romashkin , V.N.; Zharmukhamedova , G.A.; Jumanova , Zh. K.; Maltseva , E.R. (Eurasian Journal of Applied Biotechnology, 2022)
Fire blight of pome fruit cultures is a dangerous quarantine disease of pome and ornamental plants of Rosaceae, caused by a Gram-negative bacterium Erwinia amylovora. For the study of the fire blight distribution and timely establishment of the threat of endemic apple species Malus sieversii infection a phytopathological study of wild fruit forests and cultural plantations of apple (Malus spp.) was carried out in Almaty region. 263 samples were collected from wild plants without visible symptoms and cultivated plants with symptoms of a fire blight - brown and necrotic young shoots that have a characteristic "shepherd’s crook" shape, blackened leaves and ovaries remaining on the affected shoots, and samples from trees with manifestations of the disease had previously been noted were collected as well. Screening of all received samples was carried out based on PCR analysis and revealed 23 positive results. Phytopathological observations and the results of PCR analysis allowed identification of the infection’s source and distribution, as well as assessment of the current state of the studied areas of wild fruit forests and adjacent cultural apple plantations in Almaty region for the presence of fire blight’s infection agent.